Cardiac autonomic neuropathy in type 2 diabetes mellitus using Bellavere’s score system - Memon, Azhar (International Journal of Health Sciences, 2017)
Objective: Determine the frequency of cardiac autonomic neuropathy (CAN) in type 2 diabetics using Bellavere’s score system. Subjects and Methods: The present cross-sectional study was conducted at the Department of Medicine, Isra University Hospital Hyderabad from March to November 2011. Sixty voluntary participants of type 2 diabetes mellitus (DM) were selected through non-probability purposive sampling. Cardiac autonomic nerve function was assessed using Bellavere’s score system. The data were analyzed on the Statistix version 10.0 (USA) using Student’s t-test, Chi-square test, one-way ANOVA, and Tukey-Cramer test (P ≤ 0.05). Results: Of 60 diabetics, CAN was observed in 29 (41.4%). Abnormal heart rate variability (HRV), valsalva ratio, 30-15th ratio, blood pressure (BP) response to standing, and handgrip was noted in 43 (61.4%), 27 (38.5%), 17 (24.2%), 5 (7.14%), and 18 (25.7%), respectively. The hemoglobin A1c was negative correlated with HRV, valsalva ratio, 30-15th ratio, and BP response to sustained handgrip; and positively correlated with BP response to standing, systolic BP, and diastolic BP. Duration of DM was not correlated with cardiac autonomic nerve function tests. Conclusion: The CAN was observed in 29 (41.4%) using Bellavere’s score system. The CAN score may be used as feasible and reproducible bedside clinical test in diabetic patients.